2016
DOI: 10.1109/tuffc.2016.2524259
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Shear Wave Speed in the Rhesus Macaques’ Uterine Cervix

Abstract: Cervical softness is a critical parameter in pregnancy. Clinically, preterm birth is associated with premature cervical softening and post-dates birth is associated with delayed cervical softening. In practice, the assessment of softness is subjective, based on digital examination. Fortunately, objective, quantitative techniques to assess softness and other parameters associated with microstructural cervical change are emerging. One of these is shear wave speed (SWS) estimation. In principle, this allows objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 55 publications
1
26
1
Order By: Relevance
“…Cervical ripening was induced in half (n=13) of the macaques via oral administration of 200 mcg of misoprostol 12 hours prior to necropsy (Huang et al, 2016). (Misoprostol is a prostaglandin routinely used to induce labor in women.)…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cervical ripening was induced in half (n=13) of the macaques via oral administration of 200 mcg of misoprostol 12 hours prior to necropsy (Huang et al, 2016). (Misoprostol is a prostaglandin routinely used to induce labor in women.)…”
Section: Methodsmentioning
confidence: 99%
“…To minimize motion artifacts, the surrounding fascia was pinned to a sound-absorbing rubber. (This procedure mirrors that used in our studies of the ex vivo human cervix (Carlson et al, 2014b), and details can be found in Huang et al (2016). )…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations